Sophoraflavanone G from Sophora alopecuroides inhibits lipopolysaccharide-induced inflammation in RAW264.7 cells by targeting PI3K/Akt, JAK/STAT and Nrf2/HO-1 pathways - Guo, Chao; Yang, Lei; Luo, Jun; Zhang, Chao; Xia, Yuanzheng; Ma, Ting; Kong, Lingyi (International immunopharmacology, 2016)
Sophoraflavanone G (SG), a prenylated flavonoid from Sophora alopecuroides, has been reported to have many pharmacological activities including anti-inflammation. However, the molecular mechanisms of its anti-inflammatory activity remain largely unclear. In this study we investigated the effects and the underlying molecular mechanisms of SG on lipopolysaccharide (LPS)-induced inflammation in RAW264.7 cells. Pretreatment with SG inhibited LPS-induced production of nitric oxide (NO) and prostaglandin E2 (PGE2) through reducing the expressions of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). SG also decreased the expressions of pro-inflammatory cytokines, tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and interleukin-1β (IL-1β), both in the protein and gene levels. Further experiments demonstrated that SG downregulated the LPS-induced upregulation of phosphorylated phosphoinositide-3-kinase and Akt (PI3K/Akt). SG also attenuated the expression of phosphorylated Janus kinase signal transducer and activator of transcription (JAK/STAT). In addition, SG upregulated heme oxygenase-1 (HO-1) expression via nuclear translocation of nuclear factor E2-related factor 2 (Nrf2). Taken together, SG may act as a natural agent to treat some inflammatory diseases by targeting PI3K/Akt, JAK/STAT and Nrf2/HO-1 pathways. [Display omitted] •SG attenuated LPS-induced production of NO, PGE2, TNF-α, IL-1β and IL-6.•SG reduced the pro-inflammatory gene expression in protein and mRNA levels.•SG inhibited the LPS-induced PI3K/Akt activation.•SG inhibited the LPS-induced JAK/STAT activation.•SG activated the Nrf2/HO-1 signaling pathway.